An Analysis of Maudy Ayunda's Code-Mixing and Code-Switching on The Merry Riana’s Podcast - Saragih, Ester; Pasaribu, Tiara Kristina; Sihite , Jubil Ezer (PROJECT (Professional Journal of English Education), 2025)
This research use code-switching and mixing, Merry Riana explores this in the audio episode "Curhat Maudy Ayunda Tentang Perempuan, Jesse Choi, dan Krisis Identitas." This podcast episode examines the obstacles of defining one's identity and surviving life. It talks about learning overseas, taking a break from a demanding work, and changes in lifestyle following marriage to Jesse Choi. To achieve this, the authors use a qualitative descriptive approach that is based on Poplack and Muysken's theories. Code mixing and code switching classifications, such as intra-sentential, tag, and inter-sentential switching, as well as insertion, alternation, and congruent lexicalization code-mixing, are then used to classify the data. The total number of data points from this episode was 100. The outcomes are as follows: The 87 code-mixing data consist of 84 (97%) insertion data, 1 (1%) congruent lexicalization data, and 2 (2%) alternation data. Additionally, only 13 code-switching data (100%) intersentential data were discovered. The podcast did not contain any instances of intrasentential or tag-switching. This study broadens our understanding of code-mixing and code-switching and emphasizes how crucial it is to examine contemporary media in order to understand how linguistic practices are evolving.